2016
DOI: 10.1002/anie.201606448
|View full text |Cite
|
Sign up to set email alerts
|

Magnesocene‐Based Electrolytes: A New Class of Electrolytes for Magnesium Batteries

Abstract: Unlike ferrocene, bis(η -cyclopentadienyl)magnesium (magnesocene, MgCp ) is slightly dissociated in solvents, such as ethers, resulting in electrolyte solutions with low conductivity. MgCp /tetrahydrofuran solutions make possible reversible magnesium plating and stripping with low over-potentials for many cycles. The Mg deposits appear with a cauliflower-like morphology. IR and NMR spectroscopy confirm that the electrolyte is stable and not decomposed during prolonged cycling. The anodic stability limit is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…[59][60][61] Interestingly,magnesium hexafluorophosphate dissolved in THF/CH 3 CN undergoes reversible magnesium deposition/stripping.H owever, the coulombic efficiencyi se xtremely low,s imilar to Mg-(TFSI) 2 . [65] Themajor drawback for commercial magnesium salts such as Mg(TFSI) 2 or Mg(BH 4 ) 4 is that they are similar in attributes. This corresponds to ad ramatic reduction of the energy density of the battery due to the lower discharge voltage and would make charging impossible due to the lack of 5V electrolytes for magnesium batteries.Inaddition, acoulombic efficiency of 50 %l eads to a9 4% loss of magnesium after 4 cycles.F urthermore,t his electrolyte,s imilar to the MACC based electrolyte requires electrochemical conditioning before deposition and dissolution of magnesium is observed.…”
Section: Commercial Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] Interestingly,magnesium hexafluorophosphate dissolved in THF/CH 3 CN undergoes reversible magnesium deposition/stripping.H owever, the coulombic efficiencyi se xtremely low,s imilar to Mg-(TFSI) 2 . [65] Themajor drawback for commercial magnesium salts such as Mg(TFSI) 2 or Mg(BH 4 ) 4 is that they are similar in attributes. This corresponds to ad ramatic reduction of the energy density of the battery due to the lower discharge voltage and would make charging impossible due to the lack of 5V electrolytes for magnesium batteries.Inaddition, acoulombic efficiency of 50 %l eads to a9 4% loss of magnesium after 4 cycles.F urthermore,t his electrolyte,s imilar to the MACC based electrolyte requires electrochemical conditioning before deposition and dissolution of magnesium is observed.…”
Section: Commercial Saltsmentioning
confidence: 99%
“…Mg) and offers no advantage over alkyl Grignards. [65] Themajor drawback for commercial magnesium salts such as Mg(TFSI) 2 or Mg(BH 4 ) 4 is that they are similar in attributes. Asingle magnesium salt is required to be non-corrosive,have both high oxidative stability and high coulombic efficiencyas well as low overpotential.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[206][207][208][209][210] ). Additionally, Mg is the fifth most abundant element on the earth's crust and third most abundant element in seawater, suggesting for its high abundance and low cost.…”
Section: Magnesium Based Anode Materialsmentioning
confidence: 99%
“…Magnesocene has also been proven to be capable of Mg plating/striping, but the extremely low conductivity and low-voltage stability hinders a practical application. [77] Recently, Arnold and co-workers reported that magnesium hexafluoroisopropylaluminate Mg[Al(hfip) 4 ) and conductivities (>6 mS/cm). [78] This conductive salt solution was synthesized via a three-step reaction.…”
Section: Electrolytes From Chloride-free Magnesium Saltsmentioning
confidence: 99%